The effect of aromatherapy on labor pain, duration of labor, anxiety and Apgar score outcome: a systematic review and meta-analysis - Yıldız Karaahmet, Aysu; Bilgiç, Fatma Şule (The European Research Journal, 2023)
Objectives: This study was conducted to conduct a systematic review and meta-analysis of studies examining the effect of aromatherapy intervention on labor pain, duration of labor, anxiety and apgar scores in primiparous women. Methods: The literature search was conducted in PubMed, CINAHL, Scopus and Science Citation Index (Web of Science) until February 2023. This study is based on the recommendations of the Cochrane guidelines. The data were analyzed using the Review Manager computer program (Version 5.4). Results: The analysis was completed with 10 studies including 950 primiparous pregnant women. The average pooled results of the studies showed that there was a significant difference in the effect of aromatherapy on labor pain (SMD: -0.68 95% CI: -0.76 to -0.60, Z = 16.32, p < 0.01) and duration (SMD: -0.36 95% CI: -0.47 to -0.25, Z = 6.40, p < 0.00001) in the latent, active, and transition phase. When the mean results of anxiety scores were examined, it was determined that the difference between the groups was significant (SMD: -15.89 95% CI: -16.78 to -14.99, Z = 34.79, p < 0.00001). Conclusions: While the aromatherapy application used in childbirth reduced the duration and pain of the latent transition and active phase of birth, it was found that it reduced the anxiety of the pregnants in the active and transition phase.